A novel Spherical fuzzy MEREC-ARAS decision framework for optimizing innovation-driven investment strategies in energy systems - Gang Kou; Fatih Baha Aydın; Serkan Eti; Serhat Yüksel; Hasan Dinçer (Energy Strategy Reviews)
Renewable energy projects need innovative investment strategies to adapt to rapidly changing technology and market conditions. These strategies increase the economic efficiency of the projects while achieving environmental sustainability goals. Despite extensive research on renewable energy investments, there is a lack of consensus on the most critical factors and strategies. This study aims to address this gap by prioritizing strategies and identifying key criteria for investors that have limited resources. A novel decision model is proposed that uses (p,q,r)-Spherical fuzzy sets to handle uncertainties in expert opinions, the multiplicative exponential ranking method (MEREC) to weight criteria and additive ratio assessment (ARAS) to rank developed countries. The main contribution of this study is that it offers a new model for prioritizing innovation-oriented investment strategies in renewable energy projects. Creating the criteria list by considering the process and results of industrial revolutions makes an important contribution to the literature. Therefore, examining the effects of past revolutions on energy and innovation ecosystems ensures that the criteria are based on scientific foundations. Additionally, considering (p,q,r)-Spherical fuzzy sets, it is possible to make more accurate decisions in systems with multiple factors and high uncertainty, such as renewable energy projects. The study emphasizes technological innovations and incentives-supports as the most critical factors for renewable energy investments. It is also concluded that the USA and England are the most successful countries with respect to the innovation-focused investment strategies in the renewable energy sector.